Koreans in Vancouver: A Short History - Baker, Don (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2008)
AbstractThe Korean-Canadian community in Vancouver is relatively new, compared to older Asian-Canadian communities such as the Chinese-Canadian and the Indo-Canadian communities. However, Koreans now constitute one of the more visible minority communities in the area. A rapid increase in immigration from Korea led to Koreans establishing churches and restaurants throughout the Vancouver area, and identifying those churches with Korean-language signs. The rise in the number of Koreans living in the southwestern corner of the BC mainland has also led to the emergence of a cluster of stores and offices in the middle of Metro Vancouver that is large enough to merit the label "Koreatown." In addition, downtown Vancouver is filled with students who have come from Korea to study English, further heightening awareness of a substantial Korean population in the Vancouver area. In just a few decades, Korean-Canadians have emerged as a significant component of the multi-cultural landscape of British Columbia.